Enhancing water resistance of earthen buildings by using admixture materials - Arpaci, E. Y. Gokyigit; Akbulut, D. Eksi; Yildiz, O. (TAYLOR & FRANCIS LTD, 2024)
This study aims to find solutions to the weak water resistance problems of earthen buildings and reduce the frequency of the periodic maintenance they require by using admixture materials in the production of soil building materials which will be tested for their effectiveness in the enhancement of earthen buildings' water resistance. In the study, the chemical and mineralogical properties of the cohesive (clayey) soil material, which is locally called 'Gavcin' and used on flat soil roofs in the Kemaliye district of Erzincan province, were determined by XRF and XRD methods whereas the grain size distributions of them were analyzed through granulometric and hydrometric analysis. For the analysis, six different admixture materials were mixed with the original material and the liquid limit (WL), plastic limit (WP), plasticity index (IP), and soil's natural unit volume weight of the original material versus the admixture-added materials were determined. Mortars were produced with original and additive materials in order to determine their physical properties. Unit volume weights, specific gravity, density, compaction-porosity, weight water absorption potential, hardened volumetric water absorption and capillary water absorption (capillarity) capacities of the produced mortars were determined on the 28th and 365th days, respectively. In terms of consistency limits, the most satisfactory experimental results were obtained from G3 and G7 samples (29.3% and 31.3% of Liquid limits and 27.9% and 27.4% of plastic limits). In addition, these two specimens were observed to be most resistant specimens to capillary suction at the end of 28 and 365 days.
Keywords: Earthen building; admixture materials; soil building material; soil stabilization; water resistance; LIME; STABILIZATION; CEMENT; Construction & Building Technology; Engineering